Reliability and equity of subject delivery competencies: Perspectives of pre-service teachers. Issue 5 (3rd September 2019) - Makura, Alfred Henry; Kalobo, Lukanda
Abstract : This study examined the reliability and equity of assessors of subject delivery competences as perceived by pre-service teachers. The participants were 310 final year student teachers from a college in Zimbabwe. They responded to a survey on their perceptions of assessor reliability and fairness of appraisal across the school curriculum. The assessors were college lecturers, classroom mentors, teachers-in-charge, and school heads (principals). Data were analysed using descriptive statistics, the Mann-Whitney U-test, and the Wald-Wolfowitz Runs. Results indicated a bias by assessors towards math and language lessons compared to the social and environmental science subjects. Therefore, reliability and equity were nested within assessor categories. Specifically, college lecturers were more likely to assess for subject delivery competencies in subjects for examination by the national examination council compared to school personnel/assessors.